Specifics of creating clinical abstract of biospecimens - O. V. Kopylova; A. I. Ershova; A. L. Borisova; V. A. Metelskaya; O. M. Drapkina (Кардиоваскулярная терапия и профилактика)
One technology that helps overcome the problem of low research reproducibility is biobanking, which involves maintaining strict quality standards at all stages. In addition to data on the biosample (detailed documentation on sampling, transportation, preparation and subsequent storage), one of the key points is the availability of information about the donor (patient). The aim of this article was to analyze creating clinical abstract of biospecimens, combining data from various biobanks and assessing the possibilities of electronic medical records and other modern technologies for this. The search for publications was carried out in the PUBMED, eLIBRARY.RU, RSCI databases. One approach to creating a clinical description is the targeted collection of information by a specially trained employee. Primary information is most often taken from the individual records of the study participant, which are developed and approved when planning work. An alternative method is the use of electronic medical records and other documents that collect information during the assessment and treatment of patients. There are also mixed types of clinical data collection, a prime example of which is the UK Biobank. Completeness, structure, and standardization are essential characteristics of clinical description associated with biospecimens. Various standards are currently being developed to unify clinical description, making biobanks and collections more available to external researchers and organizations, which is necessary for collaboration and more efficient use of stored biospecimens. Harmonization of clinical description methodology between different biobanks open up broad boundaries for large- scale research within personalized and translational medicine.